Special Education Teachers' Perceptions and Familiarity of Response to Intervention (RtI) - Hoffman, Sara (My University, 2009)
The traditional IQ-achievement discrepancy model for identification of specific learning disabilities (SLD), is soon to be replaced by a new model known as Response to Intervention (RtI). With this change in our educational framework, will also come a change in the role and function of all teachers. Of particular interest are the perceptions special education teachers have towards the implementation of RtI. The purpose of this study is to gather information related to teachers? familiarity and perceptions of the RtI paradigm.
Special Education Teachers' Familiarity and Perceptions of Response to Intervention (RtI)
Color poster with text and table describing research conducted by Sara Hoffman, advised by William R. Frankenberger.
Keywords: Response to Intervention (RtI); Remedial teaching; Learning disabled children--Education; Slow learning children--Education; Special education teachers--Attitudes; Posters